Method for assembling lithium ion button cell
By using gaskets and electrolyte to fix the separator in lithium-ion buckle battery assembly, and using materials such as polyacrylonitrile to enhance the bonding strength of the positive electrode slurry, the problems of inconsistent assembly and poor bonding performance are solved, and the battery is improved Cycle performance and test accuracy.
Patent Information
- Application Number
- CN202411701472.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium-ion buckle battery assembly method can easily lead to dislocation of positive and negative electrodes, poor bonding performance, inconsistent assembly and short circuit problems, affecting the battery pass rate and test accuracy.
By placing a gasket in the negative electrode shell and adding electrolyte to fix the diaphragm, the position of the positive electrode sheet and the diaphragm is fixed; when the lithium sheet is installed, the liquid tension of the electrolyte is used to achieve a tight bond, combining polyacrylonitrile, conductive carbon nanotubes and The positive electrode slurry composed of conductive carbon black enhances bonding strength and electron transport capability.
It effectively avoids the problems of positive and negative pole misalignment and poor bonding performance, improves assembly consistency and test accuracy, enhances the cycle performance and energy density of the battery, and reduces the risk of short circuit.
Smart Images

Figure CN119230905A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an assembling method of lithium ion button batteries. Background Art
[0002] Lithium-ion button cells are widely used in various material verifications of lithium-ion batteries due to their advantages such as easy assembly, small size, low cost, and short verification cycle. However, during the verification process, improper assembly methods will affect the initial efficiency, gram capacity, uniformity of the SEI film, and consistency of the assembled half-cells of the positive and negative electrode materials, and may even cause battery short circuits and unavoidable safety hazards.
[0003] At present, the most common way to assemble lithium-ion batteries is positive electrode shell-positive electrode sheet-electrolyte-diaphragm-electrolyte-lithium sheet-gasket-spring sheet-negative electrode sheet-negative electrode shell. Although this method has a clear idea and is easy to operate, in actual operation, the electrode sheet is difficult to fix, the positive and negative electrodes are misaligned, and the battery is loose. This not only affects the qualified rate of the assembled battery and leads to low efficiency, but also easily affects the consistency of the assembled battery and reduces the accuracy of material verification. At the same time, in the assembly process of lithium-ion batteries, the battery adhesive is also directly related to the stability between the active substances of the battery electrode sheet, between the active substances and the conductive agent, and between the active substances and the current collector, thereby affecting the battery's cycle performance and rate performance. For example, the adhesive has weak adhesion to the metal current collector. During the test of cyclic charge and discharge, it is subjected to stress and the adhesion performance will continue to decline, resulting in an increase in the impedance between the electrode sheet and the slurry layer, which in turn causes inaccurate test results of the assembled battery, resulting in low qualified rate, low charge and discharge efficiency, large test errors, poor consistency and other problems in the assembled battery. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for assembling lithium-ion button batteries, which can effectively solve the problems of positive and negative pole misalignment, pole piece deviation, poor bonding performance, poor assembled battery consistency and assembled battery short circuit that occur during the existing button battery assembly process, thereby improving the assembly efficiency and verification accuracy of button batteries.
[0005] The purpose of the present invention is achieved through the following technical solutions: A method for assembling a lithium-ion button battery, comprising: Step S1, first place the negative electrode shell on the dust-free paper, then put the gasket into the negative electrode shell with the smooth surface facing upward, and gently press it with tweezers; Step S2, placing the positive electrode sheet with the side coated with the active material facing upward in the middle of the gasket, and dripping electrolyte on the positive electrode sheet to make the positive electrode sheet completely soaked; Step S3, using a dropper to drip electrolyte on the edge of the negative electrode shell, and placing one end of the diaphragm at the edge of the negative electrode shell where the electrolyte is attached to promote the electrolyte to infiltrate the diaphragm (for fixing the position of the diaphragm); then slowly lower the diaphragm to cover the entire negative electrode shell, and drip electrolyte on the diaphragm to cover the positive electrode sheet; Step S4, placing the lithium sheet with the concave surface facing upward on the dust-free paper, and dripping the electrolyte on the concave surface of the lithium sheet; using tweezers to cover the gasket on the lithium sheet and gently press it, so that the smooth surface of the gasket corresponds to the concave surface of the lithium sheet; Step S5, placing the lithium sheet in step S4 on the diaphragm in step S3 and pressing lightly; Step S6: first use tweezers to place the spring sheet in the middle of the gasket (on the lithium sheet) with the small hole of the spring sheet facing upwards, then buckle the positive electrode shell onto the negative electrode shell, and finally seal it to complete the assembly.
[0006] Based on further optimization of the above scheme, the positive electrode sheet is obtained by the following method: first, polyacrylonitrile is added to NMP solvent and stirred for 2.5 to 3.5 hours to disperse it to form a transparent and uniform solution; then, conductive carbon nanotubes are added to the transparent and uniform solution and stirred at room temperature for 0.8 to 1.2 hours, and then conductive carbon black is added to the solution and stirred for 0.8 to 1.2 hours; then, positive electrode active material is added to the solution and stirred for 3.5 to 4.5 hours to obtain a positive electrode slurry with a slurry fineness of less than 40 μm; finally, the positive electrode slurry is evenly coated on both sides of the current collector of the positive electrode sheet (double-sided coating ensures that the surface density of each single side is the same), and dried and rolled in sequence to obtain the positive electrode sheet.
[0007] Based on further optimization of the above solution, the current collector of the positive electrode sheet is made of aluminum foil.
[0008] Based on further optimization of the above scheme, in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active materials are: 2.7%~2.9%: 1.45%~1.55%: 1.45%~1.55%: 94%~94.4%; wherein the mass ratio of conductive carbon nanotubes to conductive carbon black is 1:1.
[0009] Based on further optimization of the above scheme, the ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 7.8% to 8.2% of the NMP solvent; wherein the molecular weight of polyacrylonitrile is 100 to 150W.
[0010] Based on further optimization of the above scheme, the positive electrode active material adopts lithium-cobalt fully recycled L917 lithium cobalt oxide.
[0011] Based on the further optimization of the above scheme, the drying temperature of the positive electrode sheet is 100-120°C and the drying time is 3.5-4.5h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 3.5-3.9g / cm 3 The sheet was rolled and immediately punched with a 12 mm punching die and placed in an oven at 100 to 120° C. for 3.5 to 4.5 hours.
[0012] In the process of preparing the positive electrode slurry, the present invention first combines the polyacrylonitrile adhesive with the conductive carbon nanotubes to form a three-dimensional conductive network, and then the nano-bite mechanism of the carbon nanotubes and the adhesive cooperate to effectively improve the bonding ability and electron transmission ability of the positive electrode slurry; after that, conductive carbon black is added, firstly, the three-dimensional conductive network is uniformly filled with conductive carbon black, thereby increasing the electron transmission path, reducing the electron transmission distance, and further increasing the electron transmission ability, and secondly, the three-dimensional network formed first is used as a skeleton structure to guide the conductive carbon black to avoid agglomeration and the distribution of conductive carbon black when adding conductive carbon black, thereby effectively ensuring the uniform transmission of electrons and the uniform adhesion of the positive electrode slurry. In addition, through the polyacrylonitrile adhesive and the specific positive active material, a strong hydrogen bond force and dipole force are formed, thereby further improving the adhesion effect of the positive electrode slurry, reinforcing the stability of the three-dimensional conductive network during the cycle, and increasing the flexibility and mechanical strength of the positive electrode sheet.
[0013] Based on further optimization of the above solution, the positive electrode shell, the negative electrode shell and the spring sheet adopt a CR2032 kit.
[0014] Based on further optimization of the above solution, the size of the lithium sheet is 16*0.4 mm; the gasket is made of stainless steel and its size is 16*0.5 mm.
[0015] Based on further optimization of the above solution, Celgard 2320 is used as the diaphragm.
[0016] Based on further optimization of the above scheme, the electrolyte adopts a lithium hexafluorophosphate solution with a concentration of 0.9-1.1 mol / L, and its solvent is a mixed solution of ethylene carbonate, dimethyl carbonate and diethyl carbonate, and the volume ratio of ethylene carbonate, dimethyl carbonate and diethyl carbonate is 2.8-3.2:4.5-5.5:1.8-2.2; wherein, four drops of electrolyte are dripped on the positive electrode sheet in step S2, one-fifth drop of electrolyte is dripped on the edge of the negative electrode shell in step S3, and one drop of electrolyte is dripped on the diaphragm, and half a drop of electrolyte is dripped on the concave surface of the lithium sheet in step S4.
[0017] The following are the technical effects of the solution of the present invention: The present application installs the negative electrode shell first, that is, inverts the negative electrode shell, so as to use the space inside the negative electrode shell to match the gasket, thereby ensuring that the positions of the positive electrode sheet and the diaphragm are fixed during the battery installation process and avoiding misalignment of the positive and negative electrodes; during the diaphragm installation process, a small amount of electrolyte is adhered to the edge of the negative electrode shell to effectively fix the diaphragm and avoid multiple adjustments of the diaphragm position. At the same time, the electrolyte and the diaphragm's own gravity are used to make the diaphragm completely cover the positive electrode sheet, which not only ensures a close fit between the two, but also effectively prevents the positive electrode sheet from curling; at the same time, during the lithium sheet installation process, the lithium sheet and the gasket are tightly combined by dripping electrolyte and using liquid tension, thereby avoiding slippage of the lithium sheet during installation, reducing the risk of misalignment, and improving the consistency of installation.
[0018] In addition, in the preparation process of the positive electrode sheet, the positive electrode slurry composed of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active materials does not contain any toxic and harmful substances, which meets the environmental protection requirements of the positive electrode sheets of current lithium-ion batteries; at the same time, the positive electrode slurry improves the bonding strength between the positive electrode active material and the positive electrode current collector under the premise of reducing the amount of adhesive used through the above-mentioned combined formula and preparation means, ensuring uniform and tight adhesion between the positive electrode slurry and the positive electrode current collector, effectively increasing the loading amount of the active material in the electrode, not only enhancing the battery cycle performance between the positive electrode active material and the positive electrode current collector, but also improving the energy density of the battery, ensuring the uniform transmission of electrons in the battery, thereby improving the overall performance of the battery. The positive electrode sheet provided in this application can be firmly bonded to the diaphragm, gasket, electrolyte, etc., which is helpful to exert the gram capacity of the positive electrode material, improve the charging and discharging efficiency and performance of the lithium-ion battery, and increase the service life of the lithium-ion battery, and provide accurate and effective support for the testing and verification of lithium-ion button batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the assembly structure of a lithium-ion button battery in an embodiment of the present invention.
[0020] Figure 2 This is a TG test chart of the adhesive prepared in Example 2 of the present invention.
[0021] Figure 3 Schematic diagram of the capacity retention rate of button cells prepared in the embodiments of the present invention and the comparative examples at 25° C. and 1C / 1C cycles for 50 weeks.
[0022] Among them, 1. negative electrode shell; 2. gasket; 3. positive electrode sheet; 4. electrolyte; 5. diaphragm; 6. lithium sheet; 7. spring sheet; 8. positive electrode shell. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0024] Embodiment 1: A method for assembling a lithium-ion button battery, comprising: Step S1, first place the negative electrode shell 1 on dust-free paper, then put the gasket 2 into the negative electrode shell 1 with the smooth surface facing upward, and gently press with tweezers to make the gasket 2 in good contact with the negative electrode shell 1; Step S2, placing the positive electrode sheet 3 with the side coated with the active material facing upward in the middle of the gasket 2, and dripping four drops of electrolyte 4 on the positive electrode sheet 3 to make the positive electrode sheet 3 completely soaked; Step S3, using a dropper to drip one fifth of a drop of electrolyte 4 on the edge of the negative electrode shell 1 (i.e., the dropper mouth is in contact with the edge of the negative electrode shell 1 to drip the electrolyte 4), and placing one end of the diaphragm 5 on the edge of the negative electrode shell 1 where the electrolyte 4 is attached to promote the electrolyte 4 to infiltrate the diaphragm 5 (for fixing the position of the diaphragm 5); then slowly lower the diaphragm 5 to cover the entire negative electrode shell 1, and drip a drop of electrolyte 4 on the diaphragm 5 to cover the positive electrode sheet 3 (through its own gravity) (to prevent the positive electrode sheet 3 from curling); Step S4, place the lithium sheet 6 with the concave surface facing upward on the dust-free paper, and drip half a drop of electrolyte 4 on the concave surface of the lithium sheet 6; use tweezers to cover the gasket 2 on the lithium sheet 6 and press gently (so that the lithium sheet 6 and the gasket 2 form a whole), and the smooth surface of the gasket 2 corresponds to the concave surface of the lithium sheet 6; Step S5, placing the lithium sheet 6 in step S4 on the separator 5 in step S3, and gently pressing (so that the synthetic lithium sheet 6 fills the negative electrode shell 1); Step S6: first use tweezers to place the spring sheet 7 in the middle of the gasket 2 (on the lithium sheet 6) with the small hole of the spring sheet 7 facing upwards, then buckle the positive electrode shell 8 on the negative electrode shell 1, and finally seal it to complete the assembly.
[0025] Among them, the positive electrode sheet 3 is obtained by the following method: first, polyacrylonitrile is added to the NMP solvent, stirred for 2.5 hours, and dispersed to form a transparent and uniform solution; the ratio of polyacrylonitrile to the NMP solvent is: polyacrylonitrile accounts for 7.8% of the NMP solvent, wherein the molecular weight of polyacrylonitrile is 100W. Subsequently, conductive carbon nanotubes are first added to the transparent and uniform solution, and fully stirred for 0.8 hours at room temperature, and then conductive carbon black is added to the solution and fully stirred for 0.8 hours. After that, the positive electrode active material is added to the solution, and the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and fully stirred for 3.5 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 2.7%: 1.45%: 1.45%: 94.4%. Finally, the positive electrode slurry is evenly coated on both sides of the aluminum foil (double-sided coating ensures that the surface density of each side is the same. In this embodiment, the surface density is maintained at 12 mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 100℃, and the drying time is 4.5h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 3.5g / cm 3 The positive electrode sheet 3 was obtained by rolling and punching with a 12 mm punching mold immediately after rolling. The positive electrode sheet 3 was placed in an oven at 100° C. and kept for 4.5 hours.
[0026] The positive electrode shell 8, the negative electrode shell 1 and the spring sheet 7 are made of CR2032 kit; the size of the lithium sheet 6 is 16*0.4mm; the gasket 2 is made of stainless steel, and its size is 16*0.5mm.
[0027] Celgard 2320 was used as the separator 5 .
[0028] The electrolyte 4 uses a lithium hexafluorophosphate solution with a concentration of 0.9 mol / L, and its solvent is a mixed solution of ethylene carbonate, dimethyl carbonate, and diethyl carbonate, and the volume ratio of ethylene carbonate, dimethyl carbonate, and diethyl carbonate is 2.8:5.4:1.8;.
[0029] Embodiment 2: A method for assembling a lithium-ion button battery, comprising: Step S1, first place the negative electrode shell 1 on dust-free paper, then put the gasket 2 into the negative electrode shell 1 with the smooth surface facing upward, and gently press with tweezers to make the gasket 2 in good contact with the negative electrode shell 1; Step S2, placing the positive electrode sheet 3 with the side coated with the active material facing upward in the middle of the gasket 2, and dripping four drops of electrolyte 4 on the positive electrode sheet 3 to make the positive electrode sheet 3 completely soaked; Step S3, using a dropper to drip one fifth of a drop of electrolyte 4 on the edge of the negative electrode shell 1 (i.e., the dropper mouth is in contact with the edge of the negative electrode shell 1 to drip the electrolyte 4), and placing one end of the diaphragm 5 on the edge of the negative electrode shell 1 where the electrolyte 4 is attached to promote the electrolyte 4 to infiltrate the diaphragm 5 (for fixing the position of the diaphragm 5); then slowly lower the diaphragm 5 to cover the entire negative electrode shell 1, and drip a drop of electrolyte 4 on the diaphragm 5 to cover the positive electrode sheet 3 (through its own gravity) (to prevent the positive electrode sheet 3 from curling); Step S4, place the lithium sheet 6 with the concave surface facing upward on the dust-free paper, and drip half a drop of electrolyte 4 on the concave surface of the lithium sheet 6; use tweezers to cover the gasket 2 on the lithium sheet 6 and press gently (so that the lithium sheet 6 and the gasket 2 form a whole), and the smooth surface of the gasket 2 corresponds to the concave surface of the lithium sheet 6; Step S5, placing the lithium sheet 6 in step S4 on the separator 5 in step S3, and gently pressing (so that the synthetic lithium sheet 6 fills the negative electrode shell 1); Step S6: first use tweezers to place the spring sheet 7 in the middle of the gasket 2 (on the lithium sheet 6) with the small hole of the spring sheet 7 facing upwards, then buckle the positive electrode shell 8 on the negative electrode shell 1, and finally seal it to complete the assembly.
[0030] Among them, the positive electrode sheet 3 is obtained by the following method: first, polyacrylonitrile is added to the NMP solvent, stirred for 3 hours, and dispersed to form a transparent and uniform solution; the ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 8% of the NMP solvent, wherein the molecular weight of polyacrylonitrile is 125W. Subsequently, conductive carbon nanotubes are first added to the transparent and uniform solution, and stirred for 1 hour at room temperature, and then conductive carbon black is added to the solution and stirred for 1 hour. After that, the positive electrode active material is added to the solution, and the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and stirred for 4 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 2.8%: 1.5%: 1.5%: 94.2%. Finally, the positive electrode slurry is evenly coated on the aluminum foil on both sides (double-sided coating ensures that the surface density of each single side is the same. In this embodiment, the surface density is maintained at 13mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 110℃, and the drying time is 4h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 3.7g / cm 3 The sheet was rolled and immediately punched with a 12 mm punching die and placed in an oven at 110° C. for 4 h to obtain a positive electrode sheet 3.
[0031] The positive electrode shell 8, the negative electrode shell 1 and the spring sheet 7 are made of CR2032 kit; the size of the lithium sheet 6 is 16*0.4mm; the gasket 2 is made of stainless steel, and its size is 16*0.5mm.
[0032] Celgard 2320 was used as the separator 5 .
[0033] The electrolyte 4 is a lithium hexafluorophosphate solution with a concentration of 1.0 mol / L, and its solvent is a mixed solution of ethylene carbonate, dimethyl carbonate, and diethyl carbonate, and the volume ratio of ethylene carbonate, dimethyl carbonate, and diethyl carbonate is 3:5:2.
[0034] The final adhesive was subjected to thermogravimetric analysis (TG) and the resulting curve was as follows: Figure 2 As shown, according to Figure 2 Those skilled in the art clearly know that the adhesive prepared in this embodiment has excellent thermal stability. The negative electrode interface of the lithium ion button battery finally prepared after 20 cycles of charge and discharge at 0.5C / 0.5C at 0°C is as follows: Figure 3 As shown, according to Figure 3 Those skilled in the art can clearly see that no lithium deposition occurs after 20 cycles, indicating that the lithium-ion button battery prepared in this embodiment has stable performance during continuous charge and discharge.
[0035] Embodiment 3: A method for assembling a lithium-ion button battery, comprising: Step S1, first place the negative electrode shell 1 on dust-free paper, then put the gasket 2 into the negative electrode shell 1 with the smooth surface facing upward, and gently press with tweezers to make the gasket 2 in good contact with the negative electrode shell 1; Step S2, placing the positive electrode sheet 3 with the side coated with the active material facing upward in the middle of the gasket 2, and dripping four drops of electrolyte 4 on the positive electrode sheet 3 to make the positive electrode sheet 3 completely soaked; Step S3, using a dropper to drip one fifth of a drop of electrolyte 4 on the edge of the negative electrode shell 1 (i.e., the dropper mouth is in contact with the edge of the negative electrode shell 1 to drip the electrolyte 4), and placing one end of the diaphragm 5 on the edge of the negative electrode shell 1 where the electrolyte 4 is attached to promote the electrolyte 4 to infiltrate the diaphragm 5 (for fixing the position of the diaphragm 5); then slowly lower the diaphragm 5 to cover the entire negative electrode shell 1, and drip a drop of electrolyte 4 on the diaphragm 5 to cover the positive electrode sheet 3 (through its own gravity) (to prevent the positive electrode sheet 3 from curling); Step S4, place the lithium sheet 6 with the concave surface facing upward on the dust-free paper, and drip half a drop of electrolyte 4 on the concave surface of the lithium sheet 6; use tweezers to cover the gasket 2 on the lithium sheet 6 and press gently (so that the lithium sheet 6 and the gasket 2 form a whole), and the smooth surface of the gasket 2 corresponds to the concave surface of the lithium sheet 6; Step S5, placing the lithium sheet 6 in step S4 on the separator 5 in step S3, and gently pressing (so that the synthetic lithium sheet 6 fills the negative electrode shell 1); Step S6: first use tweezers to place the spring sheet 7 in the middle of the gasket 2 (on the lithium sheet 6) with the small hole of the spring sheet 7 facing upwards, then buckle the positive electrode shell 8 on the negative electrode shell 1, and finally seal it to complete the assembly.
[0036] Among them, the positive electrode sheet 3 is obtained by the following method: first, polyacrylonitrile is added to the NMP solvent, stirred for 3.5 hours, and dispersed to form a transparent and uniform solution; the ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 8.2% of the NMP solvent, wherein the molecular weight of polyacrylonitrile is 150W. Subsequently, conductive carbon nanotubes are first added to the transparent and uniform solution, and fully stirred for 1.2 hours at room temperature, and then conductive carbon black is added to the solution and fully stirred for 1.2 hours. After that, the positive electrode active material is added to the solution, and the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and fully stirred for 4.5 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 2.9%: 1.55%: 1.55%: 94%. Finally, the positive electrode slurry is evenly coated on both sides of the aluminum foil (double-sided coating ensures that the surface density of each side is the same. In this embodiment, the surface density is maintained at 14 mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 120℃, and the drying time is 3.5h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 3.9g / cm 3 The sheet was rolled and immediately punched with a 12 mm punching die and placed in an oven at 120° C. for 3.5 h to obtain a positive electrode sheet 3.
[0037] The positive electrode shell 8, the negative electrode shell 1 and the spring sheet 7 are made of CR2032 kit; the size of the lithium sheet 6 is 16*0.4mm; the gasket 2 is made of stainless steel, and its size is 16*0.5mm.
[0038] Celgard 2320 was used as the separator 5 .
[0039] The electrolyte 4 is a lithium hexafluorophosphate solution with a concentration of 1.1 mol / L, and its solvent is a mixed solution of ethylene carbonate, dimethyl carbonate, and diethyl carbonate, and the volume ratio of ethylene carbonate, dimethyl carbonate, and diethyl carbonate is 3.2:4.6:2.2.
[0040] Comparative Example 1: A method for assembling a lithium-ion button cell, wherein the assembly method is opposite to that in Example 2, namely: positive electrode shell-gasket-positive electrode sheet-electrolyte-diaphragm-electrolyte-lithium sheet (concave surface)-electrolyte-gasket-negative electrode shell.
[0041] The preparation method of the positive electrode sheet is consistent with the preparation method in Example 2.
[0042] The positive electrode shell, negative electrode shell, spring sheet, lithium sheet, gasket, etc. are all consistent with those in Example 2; the diaphragm electrolyte is consistent with that in Example 2.
[0043] Comparative Example 2: A method for assembling a lithium-ion button battery. The battery assembly method is consistent with the assembly method in Example 2, that is, consistent with steps S1 to S6.
[0044] Among them, the positive electrode sheet is obtained by the following method: first, polyacrylonitrile is added to the NMP solvent, stirred for 3 hours, and dispersed to form a transparent and uniform solution; the ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 8% of the NMP solvent, wherein the molecular weight of polyacrylonitrile is 125W. Subsequently, conductive carbon black is added to the transparent and uniform solution, and fully stirred for 1 hour at room temperature, and then conductive carbon nanotubes are added to the solution and fully stirred for 1 hour. After that, the positive electrode active material is added to the solution, and the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and fully stirred for 4 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 2.8%: 1.5%: 1.5%: 94.2%. Finally, the positive electrode slurry is evenly coated on the aluminum foil on both sides (double-sided coating ensures that the surface density of each single side is the same. In this embodiment, the surface density is maintained at 13mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 110℃, and the drying time is 4h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 3.7g / cm 3 The positive electrode sheet was obtained by rolling and punching with a 12 mm punching mold immediately after rolling. The sheet was placed in an oven at 110° C. for 4 hours.
[0045] The positive electrode shell, negative electrode shell, spring sheet, lithium sheet, gasket, etc. are all consistent with those in Example 2; the diaphragm electrolyte is consistent with that in Example 2.
[0046] Comparative Example 3: A method for assembling a lithium-ion button cell, wherein the battery assembly method is consistent with the assembly method in Example 2, that is, consistent with steps S1 to S6. The positive electrode sheet is obtained by the following method: first, polyvinylidene fluoride (PVDF) is added to NMP solvent, stirred for 3 hours, and dispersed to form a transparent and uniform solution; the ratio of polyvinylidene fluoride (PVDF) to NMP solvent is: polyacrylonitrile accounts for 8% of NMP solvent. Subsequently, conductive carbon nanotubes are first added to the transparent and uniform solution, and stirred for 1 hour at room temperature, and then conductive carbon black is added to the solution and stirred for 1 hour. After that, a positive electrode active material is added to the solution, and the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and stirred for 4 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyvinylidene fluoride (PVDF), conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 3%: 1.5%: 1.5%: 94%. Finally, the positive electrode slurry is evenly coated on both sides of the aluminum foil (double-sided coating ensures that the surface density of each side is the same. In this embodiment, the surface density is maintained at 13 mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 110℃, and the drying time is 4h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 3.7g / cm 3 The positive electrode sheet was obtained by rolling and punching with a 12 mm punching mold immediately after rolling. The sheet was placed in an oven at 110° C. for 4 hours.
[0047] The positive electrode shell, negative electrode shell, spring sheet, lithium sheet, gasket, etc. are all consistent with those in Example 2; the diaphragm electrolyte is consistent with that in Example 2.
[0048] Table 1. Comparison of battery voltage, internal resistance, initial efficiency and specific capacity of different groups:
[0049] Table 1 shows the test data of the button battery assembled by Examples 1 to 3 and Comparative Examples 1 to 3. From the results, it can be seen that the button battery assembled by the method of the present invention has a higher voltage, a lower resistance, a lower probability of short circuit, a higher specific capacity and first efficiency of the battery, and good consistency, which effectively improves the accuracy of material evaluation. Furthermore, from Example 2 and Comparative Example 2, it can be seen that the order of adding materials has a greater influence on the resistance, that is, by combining the order of adding the conductive agent with the specific positive active material and the binder, the agglomeration of the conductive agent is effectively suppressed, the stability of the three-dimensional conductive network is enhanced, and the conductivity is enhanced.
[0050] Figure 3 It can be clearly seen that the order of adding the conductive agent and the method of combining the specific positive electrode active material with the binder will have a great impact on the capacity retention rate during the cycle.
Claims
1. A method for assembling a lithium-ion button battery, characterized in that: include: Step S1, first place the negative electrode shell on the dust-free paper, then put the gasket into the negative electrode shell with the smooth surface facing upward, and gently press it with tweezers; Step S2, placing the positive electrode sheet with the side coated with the active material facing upward in the middle of the gasket, and dripping electrolyte on the positive electrode sheet to make the positive electrode sheet completely soaked; Step S3, using a dropper to drip electrolyte on the edge of the negative electrode shell, and placing one end of the diaphragm on the edge of the negative electrode shell where the electrolyte is attached to promote the electrolyte to infiltrate the diaphragm; then slowly lower the diaphragm to cover the entire negative electrode shell, and drip electrolyte on the diaphragm to cover the positive electrode sheet; Step S4, placing the lithium sheet with the concave surface facing upward on the dust-free paper, and dripping the electrolyte on the concave surface of the lithium sheet; using tweezers to cover the gasket on the lithium sheet and gently press it, so that the smooth surface of the gasket corresponds to the concave surface of the lithium sheet; Step S5, placing the lithium sheet in step S4 on the diaphragm in step S3 and pressing lightly; Step S6: first use tweezers to place the spring sheet in the middle of the gasket with the small hole of the spring sheet facing upwards, then buckle the positive electrode shell onto the negative electrode shell, and finally seal it to complete the assembly.
2. The method for assembling a lithium-ion button cell according to claim 1, characterized in that: The positive electrode sheet is obtained by the following method: first, polyacrylonitrile is added to NMP solvent, and stirred for 2.5 to 3.5 hours to disperse it to form a transparent and uniform solution; then, conductive carbon nanotubes are added to the transparent and uniform solution, and fully stirred for 0.8 to 1.2 hours at room temperature, and then conductive carbon black is added to the solution and fully stirred for 0.8 to 1.2 hours; then, positive electrode active materials are added to the solution, and fully stirred for 3.5 to 4.5 hours to obtain positive electrode slurry with a slurry fineness of less than 40 μm; finally, the positive electrode slurry is evenly coated on both sides of the current collector of the positive electrode sheet, and dried and rolled in sequence to obtain the positive electrode sheet.
3. A method for assembling a lithium ion button cell according to claim 1 or 2, characterized in that: The current collector of the positive electrode sheet is made of aluminum foil.
4. The method for assembling a lithium-ion button cell according to claim 2, characterized in that: In the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active materials are: 2.7%-2.9%: 1.45%-1.55%: 1.45%-1.55%: 94%-94.4%; wherein the mass ratio of conductive carbon nanotubes to conductive carbon black is 1:
1.
5. The method for assembling a lithium-ion button cell according to claim 2, characterized in that: The ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 7.8% to 8.2% of NMP solvent; wherein the molecular weight of polyacrylonitrile is 100 to 150W.
6. The method for assembling a lithium-ion button cell according to claim 2, characterized in that: The positive electrode active material adopts lithium-cobalt fully recycled L917 lithium cobalt oxide.
7. A method for assembling a lithium ion button cell according to claim 1 or 2, characterized in that: The positive electrode shell, the negative electrode shell and the spring sheet adopt a CR2032 kit.
8. The method for assembling a lithium ion button cell according to claim 1 or 2, characterized in that: The size of the lithium sheet is 16*0.4mm; the gasket is made of stainless steel and its size is 16*0.5mm.
9. A method for assembling a lithium ion button cell according to claim 1 or 2, characterized in that: The diaphragm is made of Celgard 2320.
10. The method for assembling a lithium ion button cell according to claim 1 or 2, characterized in that: The electrolyte adopts a lithium hexafluorophosphate solution with a concentration of 0.9-1.1 mol / L, and its solvent is a mixed solution of ethylene carbonate, dimethyl carbonate and diethyl carbonate, and the volume ratio of ethylene carbonate, dimethyl carbonate and diethyl carbonate is 2.8-3.2:4.5-5.5:1.8-2.2; wherein, four drops of electrolyte are dripped on the positive electrode sheet in step S2, one-fifth drop of electrolyte is dripped on the edge of the negative electrode shell in step S3, and one drop of electrolyte is dripped on the diaphragm, and half a drop of electrolyte is dripped on the concave surface of the lithium sheet in step S4.
